Great international demonstration in aid of the International Solidarity Fund for Spain (draft leaflet) - Labour Party (Great Britain) (1937)
021-0001-001 GREAT INTERNATIONAL DEMONSTRATION. IN AID OF THE INTERNATIONAL SOLIDARITY FUND for Spain. Speakers of international renown will speak in aid of the fund being raised in this country by the Trades Union Congress and the Labour Party on MARCH 10th. The meeting will be held in the KINGSWAY HALL, HOLBORN, commencing at 7.45 p.m. Sir Walter Citrine, General Secretary of the Trades Union Congress and President of the International Federation of Trade Unions will be in the Chair. Speakers will include Mr. C.R. Attlee, M.P., Walter Schevenels, Secretary of the International Federation of Trade Unions, Dr. F. Adler, Secretary of the Labour and Socialist International, Jean Longuet, the well-known French socialist, and a highly responsible Spanish comrade - probably M. Pascual Tomas. All these speakers will be in London to attend the International Conference, being held in London under the auspices of the International Federation of Trade Unions and the Labour and Socialist International on March 10th and 11th on the position in Spain. TICKETS are 6d. each and can be obtained at Transport House, London, S.W.1. The London Labour Party, 258-262, Westminster Bridge Road, London, S.E.1. The London Trades Council, 24, Thavies Inn, London, E.C.1. Accommodation is limited and early application should be made for tickets. 292/946/21/1